Investigation ethanol extract of Piper crocatum leaves as condyloma acuminata inhibitor using protein interaction and molecular simulation - Idrianti Idrus, Wresti Indriatmi, Rasiha Rasiha, Fadilah Fadilah (Journal of Applied Pharmaceutical Science, 2025)
Condyloma acuminata (CA) is a sexually transmitted infection that is mainly caused by the Human papillomavirus. Condyloma exhibits a considerable rate of recurrence, necessitating repeated therapies. Protein-protein network was implemented to see the underlying mechanism of CA, while molecular modeling approaches investigated the bioactive compound structure from Piper crocatum as an X-linked inhibitor of apoptosis protein (XIAP) inhibitor on CA. These simulations aid in investigating protein-protein interactions, how the enriched pathways align with the known mechanism of CA, and whether they reveal any novel insight and connection to the immune system, cytokine signaling, and intrinsic pathways for apoptosis. The results from in-silico showed the most potent compounds from P. crocatum with the lowest binding free energy for binding to XIAP included N-trans-feruloyltyramine 4′-O-β- D-glucopyranoside (NFT) and Vitexin 2″-rhamnoside (VTR) compounds (−8.62 Kcal/mol and −8.6 Kcal/mol, respectively). Investigation of bonds between NFT-XIAP of complexes showed that Asn252, Thr254, Arg258, Gly305, Ser347, Leu348, and Pro352 of the XIAP domain were essential for protein binding. NFT and VTR compounds could reduce the binding ability of XIAP proteins to NFT. Therefore, these phytochemicals from P. crocatum may be feasible drug candidates against XIAP inhibitors on CA.
Keywords: Condyloma acuminata, P. crocatum, XIAP inhibitor, molecular simulation